2010
DOI: 10.1039/b918640a
|View full text |Cite
|
Sign up to set email alerts
|

Circular compartmentalized microfluidic platform: Study of axon–glia interactions

Abstract: We describe a compartmentalized circular microfluidic platform that enables directed cell placement within defined microenvironments for the study of axon-glia interactions. The multi-compartment platform consists of independent units of radial microchannel arrays that fluidically isolate somal from axonal compartments. Fluidic access ports punched near the microchannels allow for direct pipetting of cells into the device. Adjacent somal or axonal compartments can be readily merged so that independent groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 30 publications
0
69
0
Order By: Relevance
“…1) was fabricated as previously described (23). We previously showed that these devices allow selective growth of axons in one compartment, enable isolation of cell soma from their axons, and allow independent manipulation of somal and axonal compartments (24)(25)(26). To allow cells to adhere to the device, the devices were treated with PDL and Matrigel.…”
Section: Significancementioning
confidence: 99%
“…1) was fabricated as previously described (23). We previously showed that these devices allow selective growth of axons in one compartment, enable isolation of cell soma from their axons, and allow independent manipulation of somal and axonal compartments (24)(25)(26). To allow cells to adhere to the device, the devices were treated with PDL and Matrigel.…”
Section: Significancementioning
confidence: 99%
“…This is an important advantage for separating different cell types in a co-culture [68][69][70] or even separating various parts of a specific cell line or tissue within different microenvironments and subjected to various conditions [71,72]. For example, by using confined geometries, neuronal cell bodies can be restricted to remain at specific regions of the device while their axon can penetrate into other sections [73][74][75][76]. Alternatively, a tissue can be exposed to two or more distinguished physical or biochemical conditions such as different fluid temperatures [77] or multiple biochemical gradients [78,79] formed within microfluidic devices.…”
Section: Developing Novel Microfluidic Devices and Microenvironments mentioning
confidence: 99%
“…Interface 11: 20130676 soma or the axon. Hosmane et al [70] created a multiplexed circular version of the platform which used centrifugation to enhance axonal throughput through microchannels, and demonstrated increased microglial accumulation to aid in debris clearance near the site of injured CNS axons seen in figure 5. Peyrin et al [67] developed a three-compartment microfluidic device to study simultaneous axonal degeneration and death mechanisms of CNS axons subjected to axotomy with precise spatio-temporal control.…”
Section: Microfluidic Chemical Injury Devicesmentioning
confidence: 99%
“…Spinning also (f ) enhanced axonal throughput, with no observable enhancement in (g) high-density cultures with all channels occupied by neurites. (h) A PDMS wedge can be used in the axonal compartment to (i) localize microglia (adapted from Hosmane et al [70] with permission from the Royal Society of Chemistry).…”
Section: Microfluidic Physical Injury Devicesmentioning
confidence: 99%